1995
DOI: 10.1007/bf02196923
|View full text |Cite
|
Sign up to set email alerts
|

Personality, psychopathology, and nicotine response as mediators of the genetics of smoking

Abstract: Individual differences in psychopathology, personality, and nicotine responsivity and their biological bases are evaluated as mechanisms potentially mediating smoking heritability. Smokers are more likely to be high in neurotic traits (e.g., depression, anxiety, anger) and in social alienation (psychoticism, impulsivity, unsocialized sensation-seeking, low conscientiousness, low agreeableness) and low in achievement/socioeconomic status. Psychological and biological mechanisms putatively mediating these associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
96
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(107 citation statements)
references
References 98 publications
9
96
1
1
Order By: Relevance
“…Although the pharmacologic effects of nicotine on mood are well established (Gilbert et al 1998;Masson and Gilbert 1990;Perkins et al 1992), there appears to be considerable individual variation in affective responsiveness to nicotine (Gilbert and Gilbert 1995). The present study demonstrated that individual differences in anhedonia moderated the magnitude of nicotine's effect on positive affect during a positive mood induction.…”
Section: Discussionmentioning
confidence: 47%
“…Although the pharmacologic effects of nicotine on mood are well established (Gilbert et al 1998;Masson and Gilbert 1990;Perkins et al 1992), there appears to be considerable individual variation in affective responsiveness to nicotine (Gilbert and Gilbert 1995). The present study demonstrated that individual differences in anhedonia moderated the magnitude of nicotine's effect on positive affect during a positive mood induction.…”
Section: Discussionmentioning
confidence: 47%
“…Neal Doran, Bonnie Spring, Belinda Borrelli, Dennis E. McChargue, Brian Hitsman, Raymond Niaura, and Donald Hedecker This article is available at DigitalCommons@University of Nebraska -Lincoln: http://digitalcommons.unl.edu/psychfacpub/279 uniformly accepted (Warner & Burns, 2003), its expression has prompted interest in identifying psychological and/or biological conditions that impede the ability of some continuing smokers to quit successfully (Gilbert & Gilbert, 1995;Gilbert, Gilbert, & Schulz, 1998).…”
Section: Authorsmentioning
confidence: 99%
“…It is possible that some extravert smokers have been punished in situations of social interaction, which may have contributed to a decrease in the association between smoking and extraversion. [39][40][41] Literature regarding the N factor is not consistent as well. This work has not found an association between smoking and the S scale of CPS.…”
Section: Smokers X Non-smokersmentioning
confidence: 99%
“…More neurotic individuals seem to be less inclined to quit smoking, even with all the pressure the society imposes him, and can feel more intensely the effects of nicotine as compared to most emotionally stable individuals. 39,41 However, the most recent literature is still controversial about that association. 7,16,17,20,28,33,43 Several reasons for such divergences are provided.…”
Section: Smokers X Non-smokersmentioning
confidence: 99%